2001
DOI: 10.1016/s0378-1097(01)00345-7
|View full text |Cite
|
Sign up to set email alerts
|

Adhesion of Enterococcus faecalis 1131 grown under subinhibitory concentrations of ampicillin and vancomycin to a hydrophilic and a hydrophobic substratum

Abstract: The effect of two subinhibitory antibiotic concentrations of ampicillin and vancomycin during growth on the adhesion of Enterococcus faecalis 1131 to glass and silicone rubber was studied in a parallel plate flow chamber. Initial deposition rates and numbers of adhering bacteria after 4 h were higher on hydrophilic glass than on hydrophobic silicone rubber, regardless of growth conditions. The presence of 1/4 minimal inhibitory concentration (MIC) of ampicillin during growth reduced enterococcal adhesion to bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 11 publications
(12 reference statements)
0
5
0
Order By: Relevance
“…Although there is still some controversy about the role of substratum hydrophobicity (or surface tension) in bacterial adhesion, [39,40] data from the present study indicate that substratum hydrophobicity plays a crucial role in the adhesion rates of bacteria. Regardless of the strain selected, hydrophilic UV-irradiated Ti6Al4V presents lower adhesion rates as compared with hydrophobic control surfaces (Fig.…”
Section: Physico-chemical Approach To Bacterial Adhesion and Retentionmentioning
confidence: 50%
“…Although there is still some controversy about the role of substratum hydrophobicity (or surface tension) in bacterial adhesion, [39,40] data from the present study indicate that substratum hydrophobicity plays a crucial role in the adhesion rates of bacteria. Regardless of the strain selected, hydrophilic UV-irradiated Ti6Al4V presents lower adhesion rates as compared with hydrophobic control surfaces (Fig.…”
Section: Physico-chemical Approach To Bacterial Adhesion and Retentionmentioning
confidence: 50%
“…The CaP/APC coating was expected to pass the mechanical testing, as the CaP/APC adheres firmly to the titanium surface, as was previously shown by Frauchiger. 37 The shown that persistent levels of antibiotics and antiseptics below the MIC can cause the development of resistant bacteria, 15,[17][18][19][20][21] and therefore, the amount present should remain above the MIC value for a limited time before disappearing completely. 38 The cytocompatibility experiments with hTERT fibroblasts were not so promising.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, the pictures were assessed by image analysis (NIS Elements 3.1, Czech Republic). The image analysis method is a modification of GallardoMoreno's work [36]. Adhering cells were differentiated from the background by a single gray-value threshold yielding a binary black and white image, and the parameters colonized area, number of colonies and their area were evaluated.…”
Section: Cultivation and Analytical Methodsmentioning
confidence: 99%